SYSTEMATIC LITERATURE REVIEW (SLR): USER ACCEPTANCE AND SATISFACTION WITH BYOND SERVICES BY BSI - Aida Puspita; Rosyidah Septianingrum; Siti Shofiyaturrohmah; Azkania Nabila (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
Digital transformation in the Islamic banking sector requires innovation that is responsive to user needs. The BYOND by BSI application is a form of digital transformation by Bank Syariah Indonesia in response to these dynamics. This study aims to examine customer acceptance and satisfaction with the use of the BYOND application based on five recent national studies. The research findings indicate that factors such as perceived usefulness, ease of use, trust, and Islamic banking features play a significant role in driving customer usage and loyalty. Challenges include low digital literacy and concerns about security. With a sustainable approach to feature development and digital education, BYOND has great potential to strengthen the digital Islamic banking ecosystem in Indonesia.